2010
DOI: 10.1080/00140130903342349
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between manual handling performance and recent flying experience in air transport pilots

Abstract: Modern jet transport aircraft are typically flown using the on-board automation by the pilot programming commands into the auto-flight systems. Anecdotal evidence exists suggesting that pilots of highly automated aircraft experience manual flying skills decay as a result of a lack of opportunity to practise hand-flying during line operations. The ability of a pilot to revert to basic manual control is essential, for example, in cases where the aircraft's automatic capability is diminished or when reconfiguring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 8 publications
4
30
0
Order By: Relevance
“…However, the usage of occlusion allows for a more systematic analysis of information processing under restricted conditions. The observed flightpath deviations show similar amplitudes compared to other flight simulator studies (Ebbatson et al 2010;Haslbeck and Hörmann 2016), thus indicating that the occlusion conditions in this study did affect the participants but did not lead to a complete failure in the manual flying task (Table 6). Thus, occlusion appears as an approach to generate valid data to analyze pilots' performance under conditions of restricted visual resources (see Gray et al 2008).…”
Section: Discussionsupporting
confidence: 80%
“…However, the usage of occlusion allows for a more systematic analysis of information processing under restricted conditions. The observed flightpath deviations show similar amplitudes compared to other flight simulator studies (Ebbatson et al 2010;Haslbeck and Hörmann 2016), thus indicating that the occlusion conditions in this study did affect the participants but did not lead to a complete failure in the manual flying task (Table 6). Thus, occlusion appears as an approach to generate valid data to analyze pilots' performance under conditions of restricted visual resources (see Gray et al 2008).…”
Section: Discussionsupporting
confidence: 80%
“…Morris and Leung 2006) and error (e.g. Stanton et al 2009) in addition to technological factors such as display design, HMI and automation (Lintern, Waite, and Talleur 1999;Xu, Wickens, and Rantanen 2007;Ebbatson et al 2010).…”
Section: Human Factors On the Flight Deckmentioning
confidence: 98%
“…Casner and his team concluded that basic instrument scanning and aircraft control skills are reasonably well retained when the cockpit automation is used. However, in line with Ebbatson et al [38] observed that these skills could be subject to a certain degree of "rustiness" if not well maintained. They concluded that that the quality and accuracy in the retention of cognitive resources for manual flight path control depends on the degree to which flight crews remain actively engaged in the human-machine loop of supervising the cockpit automation.…”
Section: Limits Of Expertise In Monitoring a Reliable Cockpit Automatmentioning
confidence: 64%